2022
DOI: 10.1177/09722629221129980
|View full text |Cite
|
Sign up to set email alerts
|

Job Embeddedness: Cross-cultural Comparison Between China and Pakistan During COVID-19 Pandemic

Abstract: As the COVID-19 pandemic spreads across the globe, cross-cultural studies are at the forefront of individuals’ minds. Following this line, we conducted a cross-cultural examination between Chinese and Pakistani management employees’ attitude toward job embeddedness. Survey data were collected using the English and Chinese versions of seven items exhibiting attitudes towards the employees’ job embeddedness scale in the COVID-19 pandemic setting. As, the two groups are diverse on geographic, cultural, religious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This heightened response in the Chinese context could be attributed to cultural and organizational values that emphasize trust and harmony as central to workplace relationships, as elucidated in earlier research [ 27 ]. Conversely, the slightly subdued relationship in Pakistan could be influenced by other unexplored organizational or societal factors, suggesting a need for a more context-specific investigation in future studies [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This heightened response in the Chinese context could be attributed to cultural and organizational values that emphasize trust and harmony as central to workplace relationships, as elucidated in earlier research [ 27 ]. Conversely, the slightly subdued relationship in Pakistan could be influenced by other unexplored organizational or societal factors, suggesting a need for a more context-specific investigation in future studies [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could be anchored in the deep-seated Chinese cultural values that emphasize diligence and commitment in response to trust, as elucidated in previous studies [ 27 ]. In contrast, the relationship between TC and TI was more pronounced in Pakistan, suggesting that a trust-laden organizational atmosphere in Pakistan might play a more significant role in employees' stay-or-leave decisions, potentially due to unique socio-cultural or organizational dynamics specific to the region [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Is interesting to see if the results for a country where expats workforce is higher that locals will have same results or different compared to other countries where locals are more than expats. Rafiq and Jafar [13] found that the opinions of different groups of people regarding the advantages and disadvantages of job embeddedness were affected by geographic, cultural, religious, and economic scope parameters when they examined a sample of employees from Pakistan and China, thus increasing the importance of this study for the specific geographical area. Based on that, the main scope of this paper is to develop a model that will investigate the relationship between stress, engagement, well-being, and employee resilience to organizational resilience in UAE.…”
Section: Introductionmentioning
confidence: 99%